Population genetic dynamics of an invasion reconstructed from the sediment egg bank - Möst, Markus; Oexle, Sarah; Marková, Silvia; Aidukaite, Dalia; Baumgartner, Livia; Stich, Hans-Bernd; Wessels, Martin; Martin-Creuzburg, Dominik; Spaak, Piet (Molecular ecology, 2015)
Biological invasions are a global issue with far-reaching consequences for single species, communities and whole ecosystems. Our understanding of modes and mechanisms of biological invasions requires knowledge of the genetic processes associated with successful invasions. In many instances, this information is particularly difficult to obtain as the initial phases of the invasion process often pass unnoticed and we rely on inferences from contemporary population genetic data. Here, we combined historic information with the genetic analysis of resting eggs to reconstruct the invasion of Daphnia pulicaria into Lower Lake Constance (LLC) in the 1970s from the resting egg bank in the sediments. We identified the invader as 'European D. pulicaria' originating from meso- and eutrophic lowland lakes and ponds in Central Europe. The founding population was characterized by extremely low genetic variation in the resting egg bank that increased considerably over time. Furthermore, strong evidence for selfing and/or biparental inbreeding was found during the initial phase of the invasion, followed by a drop of selfing rate to low levels in subsequent decades. Moreover, the increase in genetic variation was most pronounced during early stages of the invasion, suggesting additional introductions during this period. Our study highlights that genetic data covering the entire invasion process from its beginning can be crucial to accurately reconstruct the invasion history of a species. We show that propagule banks can preserve such information enabling the study of population genetic dynamics and sources of genetic variation in successful invasive populations.
Keywords: Animals; Population Dynamics; geologické sedimenty; Germany; Genotype; DNA, Mitochondrial; jezera; Daphnia; modely genetické; Switzerland; Švýcarsko; Gene Frequency; inbreeding; Cell Nucleus; Molecular Sequence Data; genotyp; Německo; frekvence genu; ovum; Genetic Variation; Phylogeny; buněčné jádro; Genetics, Population; Models, Genetic; molekulární sekvence - údaje; zavlečené druhy; mitochondriální DNA; Microsatellite Repeats; Sequence Analysis, DNA; populační dynamika; Inbreeding; Geologic Sediments; Lakes; Ovum; zvířata; genetické markery; sekvenční analýza DNA; fylogeneze; Introduced Species; genetická variace; mikrosatelitní repetice; populační genetika; Genetic Markers